ANALISIS PENGARUH PERTUMBUHAN EKONOMI, PENDIDIKAN, DAN TINGKAT PENGANGGURAN TERHADAP KEMISKINAN DI INDONESIA TAHUN 2013 - 2022 - Suherman, Raihan; Sakti, Rachmad Kresna (Journal of Development Economic and Social Studies, 2024)
This study examines the impact of economic growth, education, and unemployment rates on poverty in Indonesia. While numerous studies have explored these relationships, this research aims to fill the gap by utilizing recent data and the Random Effect model for panel data analysis. The objective is to understand how these variables influence poverty levels and to provide relevant policy recommendations. The methodology includes t-statistics to test the partial effects and F-statistics to test the simultaneous effects of the independent variables on the dependent variable. The findings indicate that economic growth does not significantly affect poverty, whereas education and unemployment rates have significant impacts. The conclusions suggest the importance of income redistribution policies, improving access to and quality of education, and job creation in reducing poverty. This research contributes by highlighting the crucial roles of education and unemployment in the context of poverty alleviation in Indonesia and proposes evidence-based policies to support more inclusive development.